2020
DOI: 10.1177/0954405420949211
|View full text |Cite
|
Sign up to set email alerts
|

The effect of magnesium content on drilling of Al-Mg-Ti alloy by hole electrical discharge machining process

Abstract: This study presents an experimental investigation of small hole electrical discharge machining of Al-Mg-Ti alloys. A series of drilling operations were carried out for exploring the effect of magnesium content. Holes of 2 mm diameter and 15 mm depth were drilled using tubular single-hole rotary brass electrodes. The rates of material removal and electrode wear, surface roughness, overcut, average recast layer thickness, taper height and angle were studied for Al-Mg-Ti alloys contain 2%, 4%, 6%, 8%, 10%, 12%, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
(38 reference statements)
0
6
0
1
Order By: Relevance
“…Hence, the surface becomes smoother and surface quality is better when the machined surface cools down. The effectiveness of the magnesium content on EDM drilling of Al-Mg-Ti alloy has been studied by Eyercioglu and Gov [171]. It was found that the MRR is higher when the Al-Mg-Ti alloy has more magnesium because more materials melt and vaporised during the EDM drilling process.…”
Section: Edd On Hard-to-cut Materialsmentioning
confidence: 99%
“…Hence, the surface becomes smoother and surface quality is better when the machined surface cools down. The effectiveness of the magnesium content on EDM drilling of Al-Mg-Ti alloy has been studied by Eyercioglu and Gov [171]. It was found that the MRR is higher when the Al-Mg-Ti alloy has more magnesium because more materials melt and vaporised during the EDM drilling process.…”
Section: Edd On Hard-to-cut Materialsmentioning
confidence: 99%
“…Therefore, the die sinker type’s electric discharge machining (EDM) was recommended as a potential solution over the conventional machining processes to achieve complex geometrical features with tight tolerances on Mg alloys [ 10 ]. In EDM, the discharge energy which causes temperature generation is accountable for the size of the crater formed during machining [ 11 ]. In this relation, the downscaled variant of EDM at the micro-level ( µ EDM) produces smaller discharge energy than macro-EDM amid the excess material subtraction, resulting in the expulsion of a relatively smaller amount of material towards higher precision of the machining [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…10 However, increasing Mg content augmented surface roughness and thickness of recast layer in Electrical discharge drilling of Al-Mg-Ti alloy. 11…”
Section: Introductionmentioning
confidence: 99%
“…10 However, increasing Mg content augmented surface roughness and thickness of recast layer in Electrical discharge drilling of Al-Mg-Ti alloy. 11 In recent years, Electrical Discharge Machining (EDM) has been used as an alternative method to obtain nano-porous biocompatible surfaces similar to the structure of bone. It has been found that EDMtreated surfaces have a positive effect on the biological attachment of human osteoblastic cells and support the growth of bone cells in Ti alloys.…”
Section: Introductionmentioning
confidence: 99%